2014
DOI: 10.1111/ecog.01020
|View full text |Cite
|
Sign up to set email alerts
|

Biogeography of parasitism in freshwater fish: spatial patterns in hot spots of infection

Abstract: Contrary to species occurrence, little is known about the determinants of spatial patterns of intraspecific variation in abundance, particularly for parasitic organisms. In this study, we provide a multi‐faceted overview of spatial patterns in parasite abundance and examine several potential underlying processes. We first tested for a latitudinal gradient in local abundance of the regionally most common parasite species and whether these species achieve higher abundances at the same localities (shared hot spot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 73 publications
2
15
1
Order By: Relevance
“…It is probably safe to say that densities of S. anguillae and T. opisthorchis generally covary positively across localities, at both the metacercarial and adult stages. This clashes with the results reported for these two species on a much larger spatial scale, with the two species achieving their highest metacercarial abundances in completely different places across New Zealand (Blasco-Costa et al 2015). Hotspots of infection for S. anguillae were found in the northern part of the North Island and in south-central South Island, whereas those for T. opisthorchis occurred toward the southern tip of the North Island and the west coast of the South Island.…”
Section: Discussioncontrasting
confidence: 80%
See 2 more Smart Citations
“…It is probably safe to say that densities of S. anguillae and T. opisthorchis generally covary positively across localities, at both the metacercarial and adult stages. This clashes with the results reported for these two species on a much larger spatial scale, with the two species achieving their highest metacercarial abundances in completely different places across New Zealand (Blasco-Costa et al 2015). Hotspots of infection for S. anguillae were found in the northern part of the North Island and in south-central South Island, whereas those for T. opisthorchis occurred toward the southern tip of the North Island and the west coast of the South Island.…”
Section: Discussioncontrasting
confidence: 80%
“…Various pairs of species from this set of five trematodes share either one, two, or all three hosts at different life cycle stages. Previously, spatial covariation in abundance has been investigated by Blasco-Costa et al (2015) in four of these five species; it was found that even pairs of species with identical life cycles and sharing all their hosts had completely independent patterns of abundance hotspots throughout their range. However, this earlier study focused on abundance of a single life stage, used a host-centric measure of abundance, and was performed on a very large scale (all of New Zealand) involving a broad range of environmental conditions (Blasco-Costa et al 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies should include further reporting and deciphering of interaction mechanisms and consequences (e.g., [62]) in model study systems as well as the development of a predictive theory of multi-parasite epidemics, integrating the different levels of organization and the various highlighted mechanisms [63,64]. Biogeographical studies will help to discern potential interactions between parasite species manifesting at large spatial scales by identifying the underlying processes (geographic, abiotic, biotic) that are responsible for the spatial distribution of co-occurring parasite species, and also explain their similar or dissimilar hot-spots of infection [65]. New tools such as next-generation sequencing (NGS) and network analyses will help to better interpret the complex epidemiological patterns observed at each organizational level.…”
Section: Discussionmentioning
confidence: 99%
“…organic and inorganic conditions) and/or to the host (e.g. feeding, behaviour, physiology, sex) (Blasco-Costa et al 2014;Oliveira et al 2017). Furthermore, the abundance of parasites with complex life cycles may be strongly dependent of the population density of intermediate and definitive hosts, superposing time and space (Blasco-Costa et al 2014).…”
Section: Introductionmentioning
confidence: 99%